Advances in theoretical and applied statistics - Pesarin, Fortunato; Bar-Hen, Avner; Torelli, Nicola (Studies in Theoretical and Applied Statistics, 2013)
This volume includes contributions selected after a double blind review process and presented as a preliminary version at the 45th Meeting of the Italian Statistical Society. The papers provide significant and innovative original contributions and cover a broad range of topics including: statistical theory; methods for time series and spatial data; statistical modeling and data analysis; survey methodology and official statistics; analysis of social, demographic and health data; and economic statistics and econometrics.